2019
DOI: 10.1002/jcp.28384
|View full text |Cite|
|
Sign up to set email alerts
|

Rhoifolin ameliorates titanium particle‐stimulated osteolysis and attenuates osteoclastogenesis via RANKL‐induced NF‐κB and MAPK pathways

Abstract: Prosthesis loosening is a highly troublesome clinical problem following total joint arthroplasty. Wear‐particle‐induced osteoclastogenesis has been shown to be the primary cause of periprosthetic osteolysis that eventually leads to aseptic prosthesis loosening. Therefore, inhibiting osteoclastogenesis is a promising strategy to control periprosthetic osteolysis. The possible mechanism of action of rhoifolin on osteoclastogenesis and titanium particle‐induced calvarial osteolysis was examined in this study. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 38 publications
(66 reference statements)
0
23
0
Order By: Relevance
“…As the only cell with bone resorption function in the human body, OCs can lead to imbalanced bone remodelling when overactivated (Liu et al, 2019). The expression of genes related to bone‐resorptive function, such as Atpvod2, Ctr, Ctsk, and Acp5, significantly increases during OC formation (Liao et al, 2019). Therefore, one of the aims of antiosteolytic therapy is to decrease the number of OCs and subsequent bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…As the only cell with bone resorption function in the human body, OCs can lead to imbalanced bone remodelling when overactivated (Liu et al, 2019). The expression of genes related to bone‐resorptive function, such as Atpvod2, Ctr, Ctsk, and Acp5, significantly increases during OC formation (Liao et al, 2019). Therefore, one of the aims of antiosteolytic therapy is to decrease the number of OCs and subsequent bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing amount of evidence indicates that activation of the MAPK pathway, containing three major family members (ERKs, JNKs, and p38), plays a significant role in RANKL-stimulated osteoclast differentiation and formation ( Tanaka et al., 2006 ; Liao et al., 2019 ). ERK is vital for the survival of osteoclast, and JNK and p38 are also crucial for the differentiation and function of osteoclast ( Lee et al., 2002 ; Koga et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rhoifolin, with the molecular formula C 27 H 30 O 14 , is one of the most common flavonoids and is used extensively in preclinical investigations to explore its pharmacological effects in a wide range of chronic diseases including diabetes and obesity. It is found in several citrus fruits such as bitter oranges, grapefruits, lemons, and unripe grapes [ 47 , 48 ]. Previous studies found that rhoifolin influenced several biological activities, with antioxidant [ 49 ], anti-inflammatory [ 50 ], hepatoprotective [ 51 ], and anticancer potential [ 52 ].…”
Section: Main Citrus Flavonoids With Antidiabetic Effectsmentioning
confidence: 99%